Modeling of the upwelling hydrodynamics in the Aegean Sea - SAVVIDIS, Y.G.; DODOU, M.G.; KRESTENITIS, Y.N.; KOUTITAS, C.G. (Mediterranean Marine Science, 2004)
The special features of the hydrodynamic circulation in the Aegean Sea referring to the development of regional upwelling coastal zones are studied by means of a mathematical model. The modeling effort is focused on the tracing of coastal areas, where upwelling events are frequently observed during the summer meteorological conditions. These areas are characterized by the enrichment of surface waters with nutrients and, consequently, increased fish production. The phenomenon is studied by the use of a two-layer mathematical model comprising the surface heated zone and the rest of the water column. The numerical solution of the model is based on the finite differences method. The wind shear applied over the stratified basin, with predefined density stratification and initial water-layers thickness, and the gravity and Coriolis forces taken into account, constitute the basic external factors for the generation of the hydrodynamic circulation in the area of the Aegean Sea. The calibration and the validation of the model are performed by the comparison of the model output to the data and observations reported in valid scientific sources. The aim of the paper is to demonstrate the significant contribution of numerical models to the better understanding of the hydrodynamics governing the Aegean water circulation as well as the tracing of upwelling zones.